Propuesta de procedimiento operativo estándar para la solicitud de inscripción de registro sanitario de especialidades farmacéuticas importadas por una droguería - Vásquez Muñoz, Arturo Alejandro (2019)
The objective of this report was to prepare a standard operating procedure for the application for registration in the sanitary registry of pharmaceuticals specialties imported by a drugstore, according to current regulations. A revision of the current regulations was made and a standard operational procedure to be implemented called POE-ARG001 "Registration in the Sanitary Registry of pharmaceuticals specialties " was drafted, and four formats to be used in the process, FOR-ARG-001 "Format Considerations for the Registration File of the Health Device Sanitary Registry "; FOR-ARG-002 "Checklist for the review of the registration file in the Sanitary Registry of the pharmaceuticals specialties" and FOR-ARG-003 "File Tracking Format". The Standard Operating Procedure aims to optimize the process that is carried out when it is required to request the registration of new products to be marketed by the Drugstore, reducing operational errors, making efficient use of working time, which will allow the area of affairs regulatory to obtain Sanitary Records that comply with the regulations in force according to Supreme Decree 016-2011-SA and amendments